Neonatal risk factors for functional gastrointestinal disorders in preterm infants in the first year of life - Bi, Dengqin; Jiang, Honghua; Yang, Kaiting; Guan, Ting; Hou, Lin; Shu, Guihua (The Turkish Journal of Pediatrics, 2023)
Background. An assessment of functional gastrointestinal disorders (FGIDs) in premature infants in their first year of life and neonatal factors influencing the progression of FGIDs was conducted in this research. Methods. Subjects selected for the retrospective study involved preterm infants being hospitalized in the neonatal department of Northern Jiangsu People`s Hospital from September 2018 to September 2021. Data on neonatal risk factors such as gestational age, gender, birth weight, mode of delivery, feeding pattern, antibiotic administration and addition of probiotics, duration of hospitalization, maternal history of smoking, and mental health status, were all collected and analyzed. FGIDs were diagnosed according to Rome IV criteria. Results. This study included 988 preterm infants, with 725 (73.4%) having at least one FGID, 449 (45.4%) with infant colic, 411 (41.6%) with infant regurgitation, 237 (24.0%) with infant dyschezia, 190 (19.2%) with functional constipation, and 34 (3.4%) with functional diarrhea throughout the first year of life. In total, 263 infants (26.6%) without FGID symptoms were included in the control group. Further, a higher prevalence of FGIDs was observed in preterm infants with infant colic as well as infant regurgitation in particular as being characterized by a low gestational age ( < 32 w), low birth weight (< 1.5 kg), Cesarean section, formula feeding, neonatal antibiotics use, hospitalization longer than 7 days, and maternal history of smoking. It was found from association analyses that infants exclusively breastfed in their first month of life were at lower risk for regurgitation than those in the control group. Conclusions. Unnecessary antibiotic use in the neonatal period, Cesarean delivery, passive smoking, lack of breastfeeding along with inappropriate probiotics usage are major risk factors for FGIDs, and their systematic control may be effective in reducing the susceptibility to and prevalence of FGIDs in preterm infants in the first year of life.